CUTICULAR CHEMOPROFILE OF THE FRUIT FLY DROSOPHILA SUBOBSCURA (DI PTERA, DROSOPHILIDAE) - S. Pavkovi-Lui; Marina M. Todosijevi; Tatjana T. Savi; Jelena D. Trajkovi; Mirjana T. Cvetkovi; Jovana M. Stankovi; Dragana M. Milii; Luka R. Lui; Vladimir T. Tomi; Slobodan E. Makarov; Ljubodrag V. Vujisi (Journal of Animal and Plant Sciences, 2018)
In insects, cuticular hydrocarbon (CHC) profile is involved in many important biological functions and may vary in different conditions. Among fruit fly species, Drosophila subobscura is one of the most frequently used in genetic, ecological and evolutionary research, because of its rich chromosomal polymorphism, specific behavioral repertoires and habitat preferences. In this work, we identified and quantified cuticular chemoprofile of D. subobscura. Using gas chromatography ( GC) and gas chromatography coupled with mass spectrometry ( GC-MS), 25 chemical compounds were found in males and 23 compounds were found in females. Further, ANOVA confirmed significant sexual dimorphism in cuticular chemoprofile amounts. Knowledge of cuticular chemistry could contribute to further research in D. subobscura, starting from behavioral, up to ecological, since this species is recognized as an important model system for the study and monitoring of global climate changes. in CHC biosynthetic pathways were also intensively
Keywords: Drosophila subobscura; cuticular hydrocarbons; sexual dimorphism.